2007
DOI: 10.1111/j.1365-2966.2007.11882.x
|View full text |Cite
|
Sign up to set email alerts
|

X-ray and Sunyaev-Zel'dovich scaling relations in galaxy clusters

Abstract: [Abridged] We present an analysis of the scaling relations between X-ray properties and Sunyaev-Zel'dovich (SZ) parameters for a sample of 24 X-ray luminous galaxy clusters observed with Chandra and with measured SZ effect. These objects are in the redshift range 0.14--0.82 and have X-ray bolometric luminosity L>10^45 erg/s. We perform a spatially resolved spectral analysis and recover the density, temperature and pressure profiles of the ICM, just relying on the spherical symmetry of the cluster and the hydro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
136
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(152 citation statements)
references
References 71 publications
16
136
0
Order By: Relevance
“…Moreover, we expect to have an intrinsic dispersion around the main scaling relation, which needs to be included and evaluated, so we preferred to perform a linear regression using the orthogonal BCES estimators (Bivariate Correlated Errors and intrinsic Scatter, Akritas & Bershady 1996). This approach has already been used by several groups for calibrating mass-observable scaling relations (Morandi et al 2007;Pratt et al 2009), which are expected to be characterized by power laws and so fitted by linear relations y = ax + b in the log-log plan. For each relation, both variables are normalized by a pivot close to their mean.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we expect to have an intrinsic dispersion around the main scaling relation, which needs to be included and evaluated, so we preferred to perform a linear regression using the orthogonal BCES estimators (Bivariate Correlated Errors and intrinsic Scatter, Akritas & Bershady 1996). This approach has already been used by several groups for calibrating mass-observable scaling relations (Morandi et al 2007;Pratt et al 2009), which are expected to be characterized by power laws and so fitted by linear relations y = ax + b in the log-log plan. For each relation, both variables are normalized by a pivot close to their mean.…”
Section: Methodsmentioning
confidence: 99%
“…The calibration of the L X − M relation has been the subject of many studies, mainly at low redshifts. Mass estimators are usually derived from X-ray data (Markevitch 1998;Arnaud et al 2002;Reiprich & Böhringer 2002;Popesso et al 2005;Morandi et al 2007;Pratt et al 2009;Vikhlinin et al 2009). Several attempts to use weak lensing masses have also been proposed more recently (Hoekstra 2007;Bardeau et al 2007;Rykoff et al 2008;Leauthaud et al 2010;Okabe et al 2010b).…”
Section: X-ray Scaling Lawsmentioning
confidence: 99%
“…For this reason no clear consensus has been reached on the evolution of the X-ray scaling relations, despite a number of observational studies carried out in the past decade (e.g. Vikhlinin et al 2002Vikhlinin et al , 2009aEttori et al 2004b;Kotov & Vikhlinin 2005;Maughan et al 2006;Maughan 2007;Maughan et al 2012;O'Hara et al 2006;Morandi et al 2007;Branchesi et al 2007;Pacaud et al 2007;Andreon et al 2011;Reichert et al 2011).…”
Section: Evolutionmentioning
confidence: 99%
“…Due to the intrinsic limitations of these SZ measurements, as well as the reach of the X-ray data, most of these studied were intrinsically limited to the inner regions of the clusters (e.g. Cooray 1999;McCarthy et al 2003;Morandi et al 2007). Benson et al (2004) showed that the integrated SZ flux is a more robust observable than the central values of the SZ signal and found a strong correlation with X-ray temperature using a sample of 15 clusters obtained with SuZIE and X-ray temperatures from the ASCA experiment.…”
Section: Sz Scaling Relations: Pre-survey-era Observationsmentioning
confidence: 99%
“…In the simplest case, where one considers pure gravitational collapse, cluster scaling relations are expected to follow selfsimilarity (Kaiser 1986;Sereno & Ettori 2015). X-ray scaling ⋆ asifiqbal@kashmiruniversity.net † subha@tifr.res.in ‡ biman@rri.res.in § stefano.ettori@oabo.inaf.it ¶ Dominique.Eckert@unige.ch mmalik@kashmiruniversity.ac.in relations have been widely used to test the strength of correlations between cluster properties and to probe the extent of self-similarity of clusters (Morandi et al 2007). These observations show departure from self-similarity; for example, the luminosity-temperature (Lx − T ) relation for self-similar models predict a shallower slope (Lx ∝ T 2 ) than observed (Lx ∝ T 3 ).…”
Section: Introductionmentioning
confidence: 99%